SUBSTANTIATION AND METHODOLOGY FOR ASSESSMENT OF HEALTHY LIFESTYLE FORMATION IN PATIENTS WITH CORONARY HEART DISEASE - M. M. Potiazhenko; G. V. Nevoitt (Проблеми екології та медицини)
Promoting healthy lifestyle (HLS) allowed the developed countries to reduce mortality. World Health Organization (WHO) has developed the “Global Action Plan for the Prevention and Control of Noncommunicable Diseases 2013-2020”. Its quintessence consists in actualization of the healthy lifestyle issue in each country in order to reduce morbidity and mortality.